2013
DOI: 10.1016/j.juro.2013.01.057
|View full text |Cite
|
Sign up to set email alerts
|

Desmopressin Add-On Therapy for Refractory Nocturia in Men Receiving α-Blockers for Lower Urinary Tract Symptoms

Abstract: Desmopressin add-on therapy for refractory nocturia in men previously treated with an α-blocker for lower urinary tract symptoms improved voiding symptoms as well as nocturia, storage symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 25 publications
1
32
1
Order By: Relevance
“…The study also demonstrated that this combination therapy improved the quality of sleep, whilst overall tolerability remained comparable to tamsulosin monotherapy . Similar results have been seen when low‐dose desmopressin was added to other α 1 ‐blockers for men with LUTS/BPH . A recently published, double‐blind, randomised, proof‐of‐concept study showed that a combination of desmopressin 25 μg and the antimuscarinic tolterodine provided a significant benefit in nocturnal void volume ( P = .034) and time to first nocturnal void ( P = .045) over tolterodine monotherapy in women with OAB and nocturnal polyuria …”
Section: Resultssupporting
confidence: 56%
“…The study also demonstrated that this combination therapy improved the quality of sleep, whilst overall tolerability remained comparable to tamsulosin monotherapy . Similar results have been seen when low‐dose desmopressin was added to other α 1 ‐blockers for men with LUTS/BPH . A recently published, double‐blind, randomised, proof‐of‐concept study showed that a combination of desmopressin 25 μg and the antimuscarinic tolterodine provided a significant benefit in nocturnal void volume ( P = .034) and time to first nocturnal void ( P = .045) over tolterodine monotherapy in women with OAB and nocturnal polyuria …”
Section: Resultssupporting
confidence: 56%
“…a turkish study [22] evaluated 45 patients with BPH and nocturia and compared the use of combined desmopressin and alfuzosin with alfuzosin monotherapy and reported 36.11 % reduction in the mean nocturia number in patients receiving combined therapy that is significantly higher than in patients receiving alfuzosin only (25.71 %). In a recent randomized placebocontrolled Korean study, [25] reported only 18.57 % reduction in the mean nocturia number upon addition of desmopressin to different α blockers. However, they included only patients with refractory nocturia unresponsive to α blockers.…”
Section: Discussionmentioning
confidence: 99%
“…The duration of the first sleep period also increased in the desmopressin group, which significantly improved the quality of sleep versus placebo [88]. Desmopressin add-on therapy is also effective in improving nocturia and storage symptoms in men receiving an alpha blocker for LUTSs [89]. …”
Section: Nocturnal Polyuria Remains An Important Cause Of Oab In Tmentioning
confidence: 99%